Przenikanie się języków wiedzy i wiary w dyskursie kryzysu klimatycznego. Przypadek argumentu ekoteologicznego Bruno Latoura i radykalnej ekologicznej hermeneutyki biblijnej - Humeniuk, Monika (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2023)
We live in an age of planetary instability. The climate crisis has effectively captured the Western public imagination. State of uneasy is spreading unexpectedly widely, not only within the sciences but also within religious systems, for which nature and its problems could not previously count on particular concern. Perhaps in the face of the “lethargy of the Anthropocene” and the many ecological crises, science and religion, having agreed to an irremovable incompatibility and inconsistency, would be able to think and act long-term for the utopia of the common good, despite all their mutual prejudices. I assume that the interpenetration of the two hither to separate orders of social imagination of “knowledge” and “faith” is a kind of symptom of such a shift. In arguingbb for the validity of such an assumption, I use two examples to illustrate how the current ecological situation affects the mutual hybridization of the languageof science and the language of religion: the ecotheological argument of BrunoLatour and radical ecological biblical hermeneutics.
Keywords: climate crisis; lethargy of the Anthropocene; ecotheological argument; Bruno Latour; ecological turn in theology; radical ecological hermeneutics